The Relationship Between Problem-Solving Skills and Planning Ability by Using Tower of London Test - Elbistan Birgul Damla Baber; Stubbe Tobias C. (De Gruyter, 2021)
Mathematical problem-solving skills depend on many variables and cognitive skills are one of the most important of them. The purpose of this study is to determine the routine and non-routine problem-solving skills in terms of cognitive aspects. This aims to reveal the relationship between the planning ability and mathematical problem-solving skills of secondary school children, ages 10 to 13. An empirical quantitative research was done for this purpose. For the measurement of problem-solving skills, a curriculum-based mathematics achievement test was used and for assessing the planning ability, a computerized version of the Tower of London test was used. It was applied to a total of 416 students from the fifth, sixth, and seventh grade. As a result of the statistical analysis, a positive significant relationship was found between planning ability and problem-solving skills but there were not any significant differences in terms of gender.